Do Open Access Journals Have Greater Citation Impact? A Study of Journals in Health and Medical Sciences in India. Issue 3 (2nd October 2018) - Nazim, Mohammad; Ashar, Mohammad
Abstract: The purpose of this study is to examine the citation impact of open access (OA) and non-OA journals published in India in health and medical sciences journals and to explore whether OA journals received more citations than non-OA journals. An evaluative scientometric approach was used to analyze the citations of articles published in Indian health and medical science journals indexed in Scopus. Of the total 241 Indian health and medical science journals indexed in Scopus, 79 OA and 61 non-OA journals were selected for the study. Harzing's Publish or Perish software was used to extract the publication and citation data from Google Scholar for 2011–2016. Five alternate hypotheses were formulated to examine whether there is any difference between the impact of OA and non-OA journals. The results showed there is an obvious citation advantage for OA health and medical science journals compared with non-OA journals. However, The Mann-Whitney U Test analysis revealed no significant difference in the citations impacts of OA and non-OA journals, rejecting all the alternate hypotheses of the study. Since this study is the first to explore the citation impact of OA and non-OA journals in the subject of health and medical science published in India, it offers theoretical implication for examination of citation impact of OA and non-OA journals in other subjects. The study is a useful guide to journal publishers and health researchers providing information on where to publish and the journals to subscribe.